Enhancing quadrotor resilience in outdoor operations with real-time wind gust measurement by using LiDAR - Latif, Zohaib; Whidborne, James F.; Bhatti, Aamer Iqbal; Shahzad, Amir; Samar, Raza (World Scientific Publishing, 2026)
Unmanned Aerial Vehicles (UAVs) encounter wind gusts during outdoor operations, impacting their position holding, particularly for quadrotors. This vulnerability is amplified during the autonomous docking to outdoor charging stations. The integration of real-time wind preview information for UAV gust rejection control has become more feasible with advances in remote wind sensor technologies like LiDAR. In this study, a ground-based LiDAR system is proposed to predict wind gusts at the landing site of quadrotors. The acquired wind preview data are subsequently utilized by the Model Predictive Control (MPC) to effectively mitigate disturbances. To validate the proposed methodology, a nonlinear simulation environment has been established using LiDAR data collected from comprehensive field tests. The results demonstrate a notable improvement in the system performance compared to benchmark results. This research underscores the practical utility of real-time wind preview information, facilitated by LiDAR technology, in enhancing the overall operational resilience of UAVs, especially quadrotors, during challenging environmental conditions.
Keywords: 4013 Geomatic Engineering; 40 Engineering; 7 Affordable and Clean Energy; 4007 Control engineering, mechatronics and robotics; 4017 Mechanical engineering